THE CONTROL OF APRICOT SEED DORMANCY AND GERMINATION BY LOW TEMPERATURE TREATMENTS - SEIF EL-YAZAL, SAMIR A; EI-YAZAL, MOHAMED A (Innovare Journal of Agricultural Sciences, 2021)
Objective: Freshly harvested seeds of “Local” apricot variety were found to be dormant and did not germinate at all. A specific low-temperature stratification treatment was required to overcome seed dormancy. The most effective temperature for breaking seed dormancy, germination, and seedling growth was 5°C cold stratification (CS). Increased seed germination percentage was recorded when the period of stratification prolonged. Seedling developed from stratified seeds had better growth than those developed from non-stratified seeds. Methods: For stratification treatments, the seeds with removed endocarp were mixed with moistened sand. Afterward, they were subjected to a period of stratification at 5°C. Seeds were stratified in pots of 30 cm×40 cm. Stratified seeds were regularly irrigated once per week. To prevent the water loss during stratification upper surface of pots was covered by a sack. The following stratification was applied for apricot variety: CS for 0, 3, 6, 9, 12, and15 days in 1998 and 1999 years for “Local” variety. Results: Apricot seeds required a CS of about 15 days for “Local” variety to reach maximum germination and normal seedling growth. Moreover, when stratification period was prolonged, some of the chemical constituents of apricot seeds were increased and other was decreased. Therefore, it can be suggested that breaking of dormancy is coincided with several changes in different chemical constituents of seeds. Some of these materials increased (total, reducing and non-reducing sugars, total free amino acids, total indoles, and total and conjugated phenols) and other materials such as free phenols which decreased at seed germinations. Conclusion: The most effective temperature for breaking seed dormancy, germination, and seedling growth was 5°C CS. Increased seed germination percentage was recorded when the period of stratification prolonged. Seedling developed from stratified seeds had better growth than those developed from non-stratified seeds.